Dr. Aniketh Venkataram — Deep Plane Facelift — Bangalore - Venkataram, Aniketh (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Aniketh Venkataram, practicing in Bangalore, India. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003129; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; india; bangalore